DOCUMENTING THE UNDOCUMENTED: A REVIEW ON THAI-PHILIPPINE LABOUR POLICIES AND THE IMPACT TO UNDOCUMENTED FILIPINO MIGRANT WORKERS - Fonte, Allain Dumon (PEOPLE: International Journal of Social Sciences, 2020)
The Association of Southeast Asian Nations (ASEAN) is in the final stages of its planning for integration in the year 2025 (Valente, 2013; Novio, 2012). Different issues arise on how the focus on economic development can affect social development and impact the human rights of ASEAN citizens (Valente, 2013). One of the issues that are discussed is on migrant workers. The Philippine government sees the integration as an opportunity for more jobs since there will be an increase of exchange on economic goods, yet other labour groups see it as a “further implementation of neo-liberal polcies” (Labog in Valente 2013). The ASEAN Convention on Migrant Workers (ACMW) is focused on creating and implementing policies for skilled migrant ASEAN citizens, and the accreditation of their qualifications among ASEAN members, while there was very few mentioned on unskilled and undocumented workers (Chalamwong, 2012; Hall et. al., 2012; Valente, 2013). This research presents one of the flaws in the system as two members of ASEAN (Philippines and Thailand) have different existing laws, lack laws in accordance with international conventions, and weak implementations of effective laws that led to the increase and abuse of undocumented Filipino workers in Thailand. The research will challenge both states as to accountability and their action plans to change the conditions of Filipino migrant workers, and then improve the policies on ACMW for the benefit of all undocumented workers in the region.